The mechanism of alcohol craving - Türkcan, Ahmet (Journal of Dependence, 2002)
This paper reviews various models of craving that researchers have developed in recent years to explain the clinical phenomenon and underlying mechanism of alcohol craving. During the past 10 years, an increasing number of theoretical models have been developed to explain alcohol craving. A better understanding of these mechanisms, could lead to improved behavioral and pharmacological approaches for the treatment of alcohol dependence. From a phenomenological perspective, craving has been considered a manifestation of alcohol dependence. Traditional models of craving have been based primarily on the concept of classical and operant conditioning. In recent years, however, researchers have introduced cognitive concepts into their conceptualization of craving. Neurobiological and brain-imaging studies have identified numerous neurotransmitters and brain regions that may be involved in craving. These data have led to development of a neuroanatomical model. The neuroadaptive model of craving proposes that chronic alcohol exposure leads to changes in brain cell functions. In the last section of this paper present and new approaches for measurement of craving have also been reviewed.